Toward a Convergence or Divergence of Adult Learning and Education Policies? - Mikulec, Borut (2022)
In this paper we draw on the theoretical perspective of new institutionalism, particularly on that of world culture and world polity, and discuss the influence of policies of three selected international intergovernmental organisations (IIOs) concerning the recognition of prior learning (RPL) on adult learning and education (ALE) policies, of which RPL is a part, in one developing country from the global South (India) and one developed country from the global North (Germany). Based on a comparative analysis of two country cases, we show that there is evidence of a worldwide convergence of ALE policies as IIOs play a crucial role in the formation and dissemination of European and/or global RPL policies that are based on similar standards. However, it is also evident that this does not indicate a wholesale implementation and adoption of policies, especially in local environments.